Analysis Determinant Sustainable Competitive Advantage Quality Product: (Study on Welding Workshop Business in Blitar Regency) - Guntarayana, Indria (Universitas Islam Balitar, 2023)
Departure with the aim of analyzing, knowing and explaining the business implications of Determinant Competitive Quality Products in the welding workshop business in Blitar Regency. Product quality is a concern for companies if the products produced want to remain competitive in the market. This study used a mixed-method. The results show that product quality affects innovation, innovation affects competitive advantage, products affect trust, trust has a weak effect on competitive advantage, innovation has a significant effect on sustainable competitive advantage and is structured in an AVAC strategy formulation, Activities carried out by the welding workshop business are producing quality products, Value Component in this welding workshop business there are several dominant values, namely product quality, innovation and competitive advantage, Appropriability in the welding workshop business pays attention to product quality, innovation, trust, Change is the creation of the characteristics of the resulting product.